Editorial: Spatial Justice in Europe. Territoriality, Mobility and Peripherality - Papadopoulos, Apostolos G. Autor (IGiPZ PAN, 2019)
The discussion surrounding the impact of territorial cohesion policy, and the territorial prioritization of cohesion policy, can offer significant insights by problematizing spatial justice. The notions of territoriality, mobility and peripherality are presented and analyzed due to their relevance to territorial cohesion, but also because they may strengthen the concept of spatial justice. The main objective of this paper, and by extension of this issue, is to stress the relevance of spatial justice as a concept created to address socio-spatial and territorial inequalities and useful when framing policy strategies, articulating policy goals, implementing policies, or taking actions to mitigate socio-spatial inequalities. The paper is organized in four sections. The introductory section presents social and economic inequalities as signifiers of the (un)sustainability of the European project and stresses the challenges facing territorial cohesion policy. The second section includes a conceptualization of spatial justice which plays to both the analytical strength and normative rigour of the concept. Third, there is a brief discussion of the notions of territoriality, mobility and peripherality. The final section is dedicated to a description of the basic features of the six papers included in this issue.
Każdy numer posiada własny tytuł.
Keywords: mobilność; peryferyjność; nierówności społeczno-przestrzenne; sprawiedliwość przestrzenna; terytorium